The evaluation of mechanical properties graphene nanoplatelets reinforced polylactic acid nanocomposites - N. F., Ab Ghani; M. S. Z., Mat Desa; M., Bijarimi (Elsevier Ltd, 2021)
Polylactic acid (PLA) has interesting properties i.e., biodegradability, good processability, high tensile strength and stiffness. However, further enhancement on the overall properties of PLA is required to meet industrial application requirements. The addition of nanofillers, such as graphene nanoplatelets (GNP), may improve the mechanical properties, electrical and flame retardant properties of PLA. This study will focus on the use of GNP to improve PLA mechanical properties. The contents of GNP varied at 0, 0.1, 0.3, 0.5 and 1.0 wt%, and the PLA/GNP nanocomposites were prepared using twin-screw extruder by melt-blending technique, followed by injection moulding. The nanocomposites were analysed using tensile test for mechanical testing while using field emission scanning electron microscopy (FESEM) to analyse morphology. At low GNP contents, the prepared nanocomposites showed a significant improvement in tensile properties. The tensile strength of nanocomposites increased significantly when an increased GNP content in PLA and reached a maximum value at PLA with 0.3 wt% GNP (50.3 MPa) compared to others composition. FESEM results also show that the GNP dispersed uniformly in the polymer matrix of PLA/0.3GNP. Based on this study, PLA/GNP nanocomposites that contains 0.3 wt% GNP showed the best mechanical properties among all formulation.